1197 Utility of Fitbit Charge 2 for Sleep Monitoring in Patients With Obstructive Sleep Apnea. (27th May 2020) - Kim, D; Shin, W; Byun, J
Abstract: Introduction: The wearable device may be useful in monitoring sleep. Many studies reported reliable data in detecting sleep-wake states and sleep stage proportion in healthy adults, However, only a few validation studies were performed evaluating sleep using the wearable devices in patients with obstructive sleep apnea(OSA), which showed insufficient accuracy. We aimed to evaluate the reliability of multi-sensory wristband (Fitbit Charge 2) in patients with OSA. Methods: This was a preliminary analysis of a prospective single-center observational study. Consecutive patients underwent standard Polysomnography (PSG) for evaluation of OSA with Fitbit Charge 2. Sleep data from PSG and Fitbit charge 2 were compared using paired t-tests and Bland-Altman plots. Results: A total of eighty-six patients were analyzed. Four of them had poor data quality, 18 of them did not show sleep stages. Compared with the PSG, Fitbit Charge 2 showed higher total sleep time (419.1±194.0 vs 269.8±22.6, p<0.001) and sleep efficiency (95.8±2.5 vs 84.6±7.1, p<0.001). Those with sleep stage data showed higher sleep efficacy (87.7±5.5 vs 82.37.5, p=0.024) and a lower proportion of N1 sleep (33.7±19.9 vs 65.3±38.8, p=0.01). Conclusion: Fitbit Charge 2 showed limited utility in monitoring sleep in patients with obstructive sleep apnea. Support: none